AKTIVITAS ANTI BAKTERI FORMULASI LOTION EKSTRAK ETANOL RIMPANG JERINGAU PUTIH - Emilda Sari; Linda Triana; Sugito Sugito; Edy Suwandi (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2023)
Background: The skin is the most important and largest organ of the human body. The skin needs so much attention, both in terms of disease and health,because it turns out that the skin itself is quite susceptible to bacterial and fungal attacks. Therefore, the formulation of lotions for the skin, namely ingredients that can kill bacteria or fungi and are safe for the skin can be justified. Natural ingredients that have properties as antibacterial ingredients for the skin are White Jeringau. Aims:The purpose of this study was to explain the differences in the inhibition of the lotion formulation of the ethanol extract of the White Jeringau Rhizome against the growth of Staphylococcus aureus bacteria using the diffusion method. Methods:The research method used is a quasi-experimental with purposive sampling technique. The sample in this study was the lotion of the ethanol extract of the Jeringau Putih rhizome with concentrations of 40%, 50% and 60% which were replicated 9 times each so that the number of samples in this study were 27 samples. Furthermore, the sample was tested for inhibition of Staphylococcus aureus bacteria by diffusion method. Results:Based on the results of this study in 2022, antibacterial analysis of the white jeringau extract lotion sample formula I, formula II and formula III against Staphylococcus aureus bacteria using the Kirby-bauer diffusion method showed the results of the inhibition zone diameter, namely in formula I the average inhibition zone formed was 11 .50 mm, in formula II it is 13.61 mm and in formula III it is 14.50 mm. According to Davis and Stout (1971) the inhibitory response by active ingredients is grouped into 4categories, namely weak activity (? 5 mm), moderate (5-10 mm), strong (10-20 mm), and very strong (? 20 mm). Conclusion:Based on this classification, white jeringau extract lotion formula I, formula II and formula III are categorized as strong. Formula Ihad the best inhibitory response because the concentration of the extract was the smallest and had a strong category of inhibition compared to formula II and formula III which had a higher concentration and had the same inhibitory power. the results of statistical test analysis using the Kruskal Walis test obtained p value = 0.000 0.05 and it was concluded that there were differences in the white jeringau rhizome lotion formula I, II, and III in inhibiting the growth of Staphylococcus aureus bacteria.